2016
DOI: 10.1097/igc.0000000000000712
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic Outcomes of Stage IVB or Persistent or Recurrent Cervical Carcinoma Patients Treated With Chemotherapy at Siriraj Hospital: Thailand’s Largest Tertiary Referral Center

Abstract: ObjectivesTo determine response rate and survival outcomes of chemotherapeutic treatment in stage IVB, persistent, or recurrent cervical carcinoma patients.MethodsMedical records of stage IVB or persistent or recurrent cervical carcinoma patients who received chemotherapy from January 2006 to December 2013 were retrospectively reviewed. Patients with neuroendocrine carcinoma and patients who received only 1 cycle of chemotherapy were excluded. The demographic data, tumor characteristics, chemotherapeutic agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Reported PFS times and OS times ranged from 5.6 to 6.9 months and 11.6 to 18.3 months, respectively. Japanese and Thai studies showed favorable oncologic outcomes compared to outcomes reported in several Gynecologic Oncology Group (GOG) studies [4, 6, 1417]. Individual host-related factors might be major prognostic indicators related to survival, including BMI, performance status, distant metastasis, and systemic inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported PFS times and OS times ranged from 5.6 to 6.9 months and 11.6 to 18.3 months, respectively. Japanese and Thai studies showed favorable oncologic outcomes compared to outcomes reported in several Gynecologic Oncology Group (GOG) studies [4, 6, 1417]. Individual host-related factors might be major prognostic indicators related to survival, including BMI, performance status, distant metastasis, and systemic inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous clinical study revealed satisfactory results from this treatment strategy, with an overall response rate of 37.8%. In that study, the lone independent clinical predictor of shorter OS was distant metastatic disease, while BMI ≥25 kg/m 2 and non-squamous cell carcinoma were found to be independent predictors of longer PFS [17]. Previous studies reported a range of response rates and survival times, with an overall response rate that varied from 22.3 to 62.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, many studies related to mCC have contained patients with both synchronous and recurrent metastatic diseases. 7 , 13–15 But the reality is they have completely different treatment patterns that may affect the prognosis of patients. 16 , 17 …”
Section: Introductionmentioning
confidence: 99%
“…Until now, many studies related to mCC have contained patients with both synchronous and recurrent metastatic diseases. 7,[13][14][15] But the reality is they have completely different treatment patterns that may affect the prognosis of patients. 16,17 Therefore, this retrospective study aimed to explore the risk factors associated with the prognosis of newly diagnosis mCC patients and to construct nomograms to facilitate clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Also, in resource-limited settings, the use of oral metronomic chemotherapy (OMC) has been described [14]. The overall response rates (ORR) from 15% to 65% have been described for various protocols in various settings of care [15][16][17][18][19][20][21][22][23][24]. There is paucity of data regarding the outcomes of systemic treatment of recurrent cervical cancer from India [20].…”
Section: Introductionmentioning
confidence: 99%